Influence of Edible Coatings on Biochemical Fruit Quality and Storage Life of Bell Pepper cv. “Yolo Wonder” - Abad Ullah; N. A. Abbasi; M. Shafique; A. A. Qureshi (Journal of Food Quality)
The present study was carried out to investigate the influence of food grade coatings on fruit quality and storage life of bell pepper cv. “Yolo Wonder” at 8±1°C with 90–95% RH for 24 days. Coating treatments were given to bell pepper fruits by dipping in aqueous solutions of gum arabic (6, 9, and 12%), Aloe vera gel (4, 5, and 6%), and cinnamon oil (0.5, 0.75, and 1%). Physicochemical characteristics as well as quality of bell pepper fruits improved in all coating treatments. Results revealed that 12% gum arabic coating exhibited significantly reduced weight loss, membrane leakage, chilling injury, and decay incidence with less increase in pH, total soluble solids, and sugar percentage, whereas appealing fruit color (L⁎, a⁎, and b⁎) along with higher values of ascorbic acid (1.84 mg/100 g), titratable acidity (0.19%), and firmness (4 N) was observed in cold storage environment. Our results clearly suggested that coating of bell pepper fruits with 12% gum arabic can maintain postharvest storage quality of bell pepper fruits.